PENYULUHAN BATUK EFEKTIF TERHADAP PENURUNAN TANDA DAN GEJALA PASIEN TUBERKULOSIS PARU (Effective Cough Technique Counseling Toward to Decrease Sign and Symptoms Pulmonary Tuberculosis Patients) - Roihatul Zahroh; Suhendrik Adi Prayitno (Fakultas Ilmu Kesehatan Universitas Gresik, 2015)
ABSTRAKÃ‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Penyuluhan teknik batuk efektif adalah pemberian informasi dan pelatihan melakukan batuk efektif untuk mengeluarkan dahak di saluran pernafasan. Tanda dan gejala tuberkulosis paru adalah sesak nafas, produksi dahak, batuk darah, nyeri dada dan wheezing. Tujuan penelitian ini adalah untuk mengetahui pengaruh penyuluhan teknik batuk efektif terhadap tanda dan gejala pasien tuberkulosis paru.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Penelitian ini menggunakan Pra Eksperimen one group pre post test design. Responden penelitian ini berjumlah 28 responden dengan menggunakan teknik purposive sampling. Variabel independen adalah penyuluhan teknik batuk efektif dan variabel dependen adalah tanda dan gejala tuberkulosis paru. Pengumpulan data menggunakan kuesioner dan observasi, kemudian dianalisis menggunakan uji Wilcoxon test dengan signifikansi ÃŽÂ±< 0,05.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Hasil penelitian didapatkan p=0,000 yang menunjukkan perbedaan pengetahuan, kemampuan batuk efektif, tanda dan gejala pasien sebelum dan sesudah penyuluhan. Hal ini berarti bahwa ada pengaruh penyuluhan batuk efektif terhadap penurunan tanda dan gejala pasien tuberkulosis paru.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Penyuluhan teknik batuk efektif dapat digunakan sebagai salah satu tindakan mandiri perawat dalam meningkatkan upaya kesembuhan pasien tuberkulosis paru.Ã‚Â Kata Kunci: Penyuluhan batuk efektif, Tuberkulosis paruÃ‚Â ABSTRACTÃ‚Â The effective cough technique counseling was providing information, training techniques for effective cough out phlegm in the respiratory tract. Signs and symptoms of pulmonary tuberculosis are dispneu, sputum, blooding cough, chest pain, and wheezing.The purpose of this study was to evaluate the effect of techniques effective techniqueÃ¢â‚¬â„¢s counseling toward cough signs and symptoms of pulmonary tuberculosis patients.This study used a pre experimental one group pre post test design. Sample were recruited using purposive sampling, taken according to inclusion criteria with sample size of 28 people who had pulmonary tuberculosis at Ibnu Sina Hospital. The independent variables in this study were cough effective counseling techniques and the dependent variables are the signs and symptoms of pulmonary tuberculosis patients. Data collection using questionnaires and observation, then analyzed using the Willcoxon test with significant ÃÂ < 0.05.From the test results obtained statistical ÃÂ value of the variable level of knowledge with 0.000 X1 = 1.46 and X2 = 2.29 which shows that there was the different between the patientÃ¢â‚¬â„¢s knowledge in pre and post test. In the variable ability to effectively cough technique ÃÂ 0.000 X1 = 1.43 and X2 = 2.93 which shows that there was the different of patientÃ¢â‚¬â„¢s ability to effective cough in pre and post test. . And variable signs and symptoms of pulmonary tuberculosis ÃÂ 0.000 patients with X1 = 1.82 and X2 = 2.64 which shows there is there is the despent the sign and symptom in patient with pulmonary tuberculosis. From the result can cleared that there is the effect of the effective cough techniques counseling toward to decrease the sign and symptoms of pulmonary tuberculosis, so that needed to increase the effective cough techniques counseling in health instantion or in non-health instantion to decrease the sign and symptom of pulmonary tuberculosis.Ã‚Â Keywords: Effective cough technique counseling , Pulmonary tuberculosis